Religious dimensions of national and European identities: evidence from cross-national survey research - Trittler, Sabine; Mandes, Sławomir; Koenig, Matthias (Religion and national identities in an enlarged Europe, 2015)
This chapter investigates how processes of European integration have affected national and European identities among the wider population. Ongoing concerns about a putative ‘democratic deficit’ in the European Union have prompted sustained research on whether or not elite-driven institution-building and identity constructions at the European level have been accompanied by the emergence of European identities among ordinary citizens. However, only recently has this line of research started to tackle the interrelation of collective identities with religion, which lies at the heart of this volume. Drawing on cross-national survey data, we therefore aim to explore how national and European identifications relate to religion across Europe. By charting differences between ‘old’ Western member states and ‘new’ member states from Eastern Europe as well as differences across confessional traditions, we additionally situate this book’s major cases — Germany, Poland, Greece, and Turkey — within broader European trends and patterns.